Drosophila Smad2 opposes Mad signaling during wing vein development. - Veronika Sander; Edward Eivers; Renee H Choi; Edward M De Robertis (PLoS ONE)
In the vertebrates, the BMP/Smad1 and TGF-beta/Smad2 signaling pathways execute antagonistic functions in different contexts of development. The differentiation of specific structures results from the balance between these two pathways. For example, the gastrula organizer/node of the vertebrates requires a region of low Smad1 and high Smad2 signaling. In Drosophila, Mad regulates tissue determination and growth in the wing, but the function of dSmad2 in wing patterning is largely unknown. In this study, we used an RNAi loss-of-function approach to investigate dSmad2 signaling during wing development. RNAi-mediated knockdown of dSmad2 caused formation of extra vein tissue, with phenotypes similar to those seen in Dpp/Mad gain-of-function. Clonal analyses revealed that the normal function of dSmad2 is to inhibit the response of wing intervein cells to the extracellular Dpp morphogen gradient that specifies vein formation, as measured by expression of the activated phospho-Mad protein. The effect of dSmad2 depletion in promoting vein differentiation was dependent on Medea, the co-factor shared by Mad and dSmad2. Furthermore, double RNAi experiments showed that Mad is epistatic to dSmad2. In other words, depletion of Smad2 had no effect in Mad-deficient wings. Our results demonstrate a novel role for dSmad2 in opposing Mad-mediated vein formation in the wing. We propose that the main function of dActivin/dSmad2 in Drosophila wing development is to antagonize Dpp/Mad signaling. Possible molecular mechanisms for the opposition between dSmad2 and Mad signaling are discussed.